2008
DOI: 10.2528/pierc08030301
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Resonant Frequency of E-Plane and H-Plane Coupled Microstrip Patch Antennas

Abstract: When a microstrip patch antenna is brought closer than 0.2λ to an identical patch the resonant frequency of that antenna changes from the designed frequency. In this paper numerical results for the resonant frequency are presented from a theoretical analysis of the mutually coupled H-plane microstrip patch antennas with confirming experimental results. We have also established the relation between resonant frequency of E-plane coupled and H-plane coupled microstrip patch antennas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…The radiation patterns at other bands, which are similar to those at 38 GHz, are not presented here in detail. It could be found that the proposed toothbrush-shaped antenna exhibits nearly omnidirectional radiation pattern in the Eplane and H-plane [10]. …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The radiation patterns at other bands, which are similar to those at 38 GHz, are not presented here in detail. It could be found that the proposed toothbrush-shaped antenna exhibits nearly omnidirectional radiation pattern in the Eplane and H-plane [10]. …”
Section: Resultsmentioning
confidence: 98%
“…Many related patch antenna designs, due to their light weight, simplicity in design and low manufacturing cost [6][7][8][9][10][11], have been demonstrated recently, such as E-shape patch 32 Yang, Li, and Liu antenna [12][13][14], U-slot antenna [15][16][17], V-shape monopole antenna [18], Planar Inverted-L Antenna [19], M-slot antenna [20], H-shaped antenna [21,22]. And broadband rectangular microstrip antenna with toothbrush-shaped slots has been proposed in the past at frequency 1800 MHz [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Antennas, which play an important role in wireless communication, are also increasingly required to become smaller, lightweight and conformal to the structure of the mobile terminal, while maintaining the high gain characteristics. In particular, it is important mentioning that the strongest limitation in antenna design for smaller wireless systems is the radiating element size [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%